The impact of BRICS trade facilitation on China’s import and export trade in agricultural products - Xin, Gao; Khan, Humayun; Ling, Xin (Frontiers in Sustainable Food Systems, 2024)
Trade facilitation is essential for enhancing the import and export of agricultural products between China and BRICS countries. Improving trade efficiency and identifying potential opportunities contribute to establishing formal cooperation mechanisms among nations, laying a robust foundation for the development and collaboration of BRICS countries post-expansion. This study developed a comprehensive indicator system and employed principal component analysis to assess trade facilitation levels among BRICS member states. Additionally, we employed a stochastic frontier gravity model to examine the trade efficiency and potential impact of BRICS trade facilitation on China's agricultural imports and exports from 2009 to 2022. The findings suggest that the overall level of trade facilitation in BRICS countries remains relatively low, with considerable scope for enhancement. The United Arab Emirates exhibits the highest level of trade facilitation, whereas Ethiopia shows the lowest. Factors such as economic status, business environment, and advancements in technology positively influence trade efficiency, while inadequate infrastructure impedes it. A notable disparity exists in the average trade efficiency of agricultural imports and exports between China and BRICS countries, with Russia displaying the highest efficiency and Iran the lowest. Brazil demonstrates significant trade potential, whereas the trade demand between Iran and China is comparatively minimal. The results are important for policymakers, pointing to the need for specialized trade policies and agricultural management strategies that reflect the diverse characteristics and challenges within BRICS economies.